2023
DOI: 10.1002/smtd.202300222
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and Self‐Healing of FAPbBr3 Perovskite under Soft‐X‐Ray Irradiation

Abstract: The extensive use of perovskites as light absorbers calls for a deeper understanding of the interaction of these materials with light. Here, the evolution of the chemical and optoelectronic properties of formamidinium lead tri‐bromide (FAPbBr3) films is tracked under the soft X‐ray beam of a high‐brilliance synchrotron source by photoemission spectroscopy and micro‐photoluminescence. Two contrasting processes are at play during the irradiation. The degradation of the material manifests with the formation of Pb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Previous studies have reported self-healing effects in FAPbBr 3 thin films. 22 However, we observe a concentration increase beyond expected levels, followed by a decline and no recovery of metallic lead to Pb 2+ . In contrast, self-healing implies an initial decrease followed by restoration of the original composition.…”
Section: Resultsmentioning
confidence: 48%
See 3 more Smart Citations
“…Previous studies have reported self-healing effects in FAPbBr 3 thin films. 22 However, we observe a concentration increase beyond expected levels, followed by a decline and no recovery of metallic lead to Pb 2+ . In contrast, self-healing implies an initial decrease followed by restoration of the original composition.…”
Section: Resultsmentioning
confidence: 48%
“…On the other hand, FAPbBr 3 depicts only slight changes in the Br 3d spectra and an increase in the N 1s peak intensity, in agreement with literature. 22 Lastly, the fully inorganic CsPbBr 3 perovskite single crystal demonstrated minimal metallic lead formation and peak broadening of the Br 3d and the Cs 4d core level spectra. Similar results were previously reported by our group for CsPbBr 3 thin films.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…More recently also Ostrikov and co-workers , reported on 60 Co γ-rays stability of CsPbBr 3 PNCs showing 90% retention of RL intensity up to 319 kGy (Figure i). The origin of such resistance to radiation damage in PNCs is still debated, whereas in bulk perovskites self-healing processes have been observed under proton, soft X-ray, and γ-ray irradiation, showing that the ionic lattice mobility in LHP prompts the recycle of the degradation byproducts trapped in the crystal and results in a complete recovery of the optoelectronic properties. The impressive hardness of PNCs is of great interest in large experiments, such as in the Large Hadron Collider at CERN, where the luminosity is already above 10 34 cm –1 s –1 and is expected to reach ∼5 × 10 35 cm –1 s –1 by 2035, resulting in an annual radiation load of over 1 MGy inside calorimeters and scintillating fiber tracking detectors. , To date, organic plastic scintillators and optical fibers have been extensively used in high-energy physics (HEP) experiments, valued for their low cost and relatively fast detection characteristics, but they suffer from prolonged radiation exposure, resulting in LY losses typically exceeding 50% above 100 kGy …”
Section: Scintillation Properties Of Pnc Nanoscintillatorsmentioning
confidence: 99%